Critical reflections on Pollitt and Bouckaert's construct of the neo-Weberian state (NWS) in their standard work on public management reform - Hubert Treiber (Theory and Society, 2022)
Pollitt and Bouckaert and their neo-Weberian state (NWS) have been chosen as the subject for this essay because the book has become a standard work in the public management movement. It is frequently cited and has been re-published in multiple editions (most recently in 2017). The authors also refer explicitly to Max Weber. This contribution seeks to draw attention to three important aspects, which inevitably overlap with one another: 1. There is no Weber in the neo-Weberian State (introduction, 1; section II). Pollitt and Bouckaert fail to grasp that Weber's understanding of the state [the state as an "institution" ( Anstalt ); and the state as an "idea of validity" ( Geltungsvorstellung )] is not identical to his ideal type of modern bureaucracy; it is the features of the latter on which they draw. The ideal type is a standard measure constructed in order to establish how close any concrete, given instance of bureaucracy comes to it (introduction, 3). Meanwhile, the "neutral official" insisted upon by Weber has "taken their leave" in Germany from important positions (section III, 3). Furthermore, Weber did not address those structures and processes internal to the administration which are precisely the object of interest for the new public management reformers. Weber's lack of interest arises from the fact the members of an Anstalt , whether it is the state or the Church (WuG, 15, no. 2), are subject to imposed orders ( oktroyierte Ordnungen ) and, as such, do not enjoy the "right to have a say". Scharpf ( 101 ) was the first to pay particular attention to the problems brought about by specialisation and by the division of labour within the administration that are responsible for an incremental form of politics (section III, 3); even if he later ascribes advantages to the combination of "negative" and "positive coordination" (Scharpf 104 : 18ff.). 2. The "legalistic culture" that characterises Germany will be considered in a more differentiated way, drawing on empirical studies which provide information, for example, on how laws (i.e. programmes) actually originate inside the ministerial apparatus (introduction, 2; section III, 2 and 3) or how use is made of the power of authority ( Weisungsrecht ) in practice (introduction, 2; section III, 2 and 3), even when, formally, it claims to have validity (section III). In this way, only empirical studies (Benz 5 ; Bohne 14 ; Dose 30 ; Dose/Voigt 31 ; Treiber 127 ) prove that the administration that implements laws has often, in practice, become a "negotiative administration" (introduction, 2). Such a phenomenon as a "co-operative administration", which negotiates rather than rules, is a "foreign concept" in Weber's discussion of the state and modern bureaucracy. Scharpf's ( 100 ) comparison between constitutional governance in Germany and legal relief in America is enlightening when it comes to the meaning of the constitutional state ( Rechtsstaat ) (introduction, 2; section III); the same applies to his discussion of the failed federalist reforms, which sought, among other things, to mitigate, if not entirely eliminate, the opportunities for blockades provided by political entanglement ( Politikverflechtung ) (section III). Neither was it possible to realise long overdue proposals to reform administrative law ( Verwaltungsrecht ) (section III, 1), which involved weakening or removing altogether three important assumptions in the dominant administrative doctrine (the "dogmatic normality") and which also included the ambitious intention for the law to achieve tangible impact (Hoffmann-Riem 49 ). Nonetheless, while no-one would dispute that reform of the federal government and administration remained "on the agenda" (Scharpf 104 , Mayntz/ Scharpf 79 ), the priorities of such a reform were, and still are, different to those of new public management reform [the key terms here are Planung ("planning") and the term that replaced it, Steuerung ("management")] 1 . 3. Pollitt and Bouckaert ascribe to the neo-Weberian state extremely varied functions without providing any (theoretical) basis for them. In this way, the notion of public management reform that they present acquires the status of a "reformist philosophy" (introduction, 3; section IV). See Scharpf ( 104 ) for a theoretically well-founded argumentation on the State's ability to act in our days. Scharpf's essay will be discussed briefly (section IV). Conclusion There is no Weber in the neo-Weberian state. According to the discussion presented here, the neo-Weberian state can only mean: how would a modern state constituted by Weber look today?
Keywords: 300; Law and Legal Studies